1, 3-ß-d-Glucan testing is highly specific in patients undergoing dialysis treatment. (January 2017) - Prattes, Juergen; Schneditz, Daniel; Prüller, Florian; Jaindl, Eva; Sauseng, Notburga; Hoenigl, Martin; Schilcher, Gernot; Krause, Robert
Summary: Background: The aim of this combined in-vitro and in-vivo study was to investigate whether state of the art dialysis modalities produce false positive serum 1, 3-ß-d -Glucan (BDG) levels. Methods: Dialysis fluid for simulated dialysis treatments was spiked with BDG from different sources. Samples were taken from the dialysate and dialyzer blood compartments at various time points. In addition, serum samples were obtained in three groups of patients without invasive fungal disease: a.) twelve patients on chronic hemodialysis (HD)/hemodiafiltration (HDF); b.) ten patients on continuous ambulatory peritoneal dialysis (CAPD); and c.) ten patients with stable chronic kidney disease (CKD) but without dialysis. Results: Median BDG levels in BDG spiked dialysate were 3250.9, 2050.4, and 390.1 pg/ml respectively. All corresponding samples from the blood compartments were BDG negative. In HD/HDF patients no increase of serum BDG levels could be observed over the duration of treatment. 71/72 BDG tests in this group remained negative. BDG tests were also negative in 9/10 CAPD patients, both in in- and outflow dialysates as well as in all ten patients with CKD. Conclusion: We conclude that state of the art renal replacement therapies using up-to-date treatments are not a cause of falsely elevated serum BDG levels. Highlights: Dialysis is not associated with false positive serum BDG levels. Synthetic state of the art dialyzer membranes do not leak nor leach BDG. False positive serum BDG levels may be associated with cellulose containing material. Avoid any contact with cellulose based material during blood sampling. Cotton swabs are a source for considerable BDG contamination.